(untitled) (The Review of Diabetic Studies, 2025)
Radiation exposure—whether medical, occupational, or environmental—remains a global public health concern due to its potential to cause cellular damage, cancer, organ dysfunction, and ecological instability. This systematic review synthesizes current evidence (2016–2025) on radiation dose-response patterns, risk determinants, and the interventions designed to mitigate exposure. Databases including PubMed, Scopus, and Web of Science were searched for observational studies, clinical trials, dosimetry research, and policy-based evaluations. Findings demonstrate that dose-response effects vary substantially across ionizing and non-ionizing radiation types, with cumulative exposure posing the highest risk. In medical contexts, diagnostic imaging contributes significantly to population-level exposure, while occupational settings involving nuclear facilities, radiology departments, and aviation present elevated chronic risks. Environmental radiation from natural sources, fallout, and industrial processes continues to influence ecosystems and vulnerable populations. Across all contexts, safety interventions—such as ALARA principles, personal protective equipment (PPE), shielding, digital monitoring, and AI-enhanced dosimetry—prove essential in reducing harm. This review highlights critical gaps in monitoring technologies, emerging radiation sources, and global disparities in safety regulations. Strengthening unified international standards and promoting precision dosimetry remain key recommendations.